Blind SLM for PAPR reduction of Alamouti DSFBC systems. Issue 3 (1st February 2017) - Fallahzadeh, Milad; Ferdosizadeh, Mahmoud
Abstract : The combination of differential space–time block codes and orthogonal frequency‐division multiplexing (OFDM) as differential space–frequency block coded (DSFBC)‐OFDM system is a good candidate to achieve maximum diversity without the need to channel estimation. High peak‐to‐average‐power ratio (PAPR) is a major drawback in these systems. The available PAPR reduction methods are not directly applicable in DSFBC‐OFDM system. In this study, the proper application of selected mapping (SLM) method for reducing PAPR in Alamouti DSFBC‐OFDM system is investigated and two different schemes are presented: conventional SLM (C‐SLM) and blind differential SLM (BD‐SLM). In C‐SLM technique, the index of the selected phase sequence must be sent to the receiver side as the side information (SI). In the proposed BD‐SLM method, specific phase mask vectors are generated with one‐to‐one correspondence with the different phase rotation sequences. Then at the receiver side, a differential minimum Hamming distance decoder is introduced to detect the index of optimum phase mask vectors without SI. Simulation results show that the proposed BD‐SLM scheme (without the need to SI) provides good performances of both the bit error rate and PAPR reduction compared with C‐SLM method.